The anatomy of a crushing bite: The specialised cranial mechanics of a giant extinct kangaroo - Mitchell, D. Rex (PLOS ONE, 2019)
The Sthenurinae were a diverse subfamily of short-faced kangaroos that arose in the Miocene and diversified during the Pliocene and Pleistocene. Many species possessed skull morphologies that were relatively structurally reinforced with bone, suggesting that they were adapted to incorporate particularly resistant foods into their diets. However, the functional roles of many unique, robust features of the sthenurine cranium are not yet clearly defined. Here, the finite element method is applied to conduct a comprehensive analysis of unilateral biting along the cheek tooth battery of a well-represented sthenurine, Simosthenurus occidentalis. The results are compared with those of an extant species considered to be of most similar ecology and cranial proportions to this species, the koala (Phascolarctos cinereus). The simulations reveal that the cranium of S. occidentalis could produce and withstand comparatively high forces during unilateral biting. Its greatly expanded zygomatic arches potentially housed enlarged zygomaticomandibularis muscles, shown here to reduce the risk of dislocation of the temporomandibular joint during biting with the rear of a broad, extensive cheek tooth row. This may also be a function of the zygomaticomandibularis in the giant panda (Ailuropoda melanoleuca), another species known to exhibit an enlarged zygomatic arch and hypertrophy of this muscle. Furthermore, the expanded frontal plates of the S. occidentalis cranium form broad arches of bone with the braincase and deepened maxillae that each extend from the anterior tooth rows to their opposing jaw joints. These arches are demonstrated here to be a key feature in resisting high torsional forces during unilateral premolar biting on large, resistant food items. This supports the notion that S. occidentalis fed thick, lignified vegetation directly to the cheek teeth in a similar manner to that described for the giant panda when crushing mature bamboo culms.